Attracting New Talent to Family Firms: Who is Attracted and under what Conditions?. (September 2016) - Hauswald, Hannes; Hack, Andreas; Kellermanns, Franz W.; Patzelt, Holger
In making a decision to enter into a long–term employment relationship with a firm, job seekers often compare their needs and values with the perceived organizational characteristics of the firm. In the case of family firms, the communication of family influence can be a unique factor in shaping beliefs about firm attributes. Family influence is often associated with trustworthiness, security, and stability. However, family influence is also associated with inflexibility and resistance to change. Using the idea of person–organization fit, we hypothesize that although family influence attracts job seekers in general, applicants who value conservation or self–transcendence are particularly attracted, while applicants who emphasize openness to change or self–enhancement are less attracted. Furthermore, we propose that the attractive effects of family influence are more pronounced in more hostile economic environments. We find evidence for our hypotheses using a conjoint experiment and 5, 600 assessments of family influence nested within 175 job seekers.